Modular Furniture System at the Office of PT. Redpot Indonesia - Anshory, Boike Janus (Pendhapa, 2023)
There are many ways to raise office employee quality. Innovating desk chair facilities to meet the demands of working methods is one of the things that can be pursued. It has been established that the working style of the employees—the majority of whom are young people—requires a productive and exciting work environment to increase the quality of work. Various approaches have been investigated to achieve the design planning of office work facilities, from recommending the design of desk chair facilities following furniture ergonomics to establishing layouts in rooms that match the characteristics of the office atmosphere. Unfortunately, interior designers frequently overlook something equally important to consider, namely the requirement that the design of seating areas related to the desks and chairs used by office workers in daily activities be adjusted to the office branding characteristics and the psychological state of the workers in the space. This study aims to give relevant parties suggestions for appropriate working desks and seating areas to carry out activities using modular furniture. A descriptive qualitative research methodology is employed. Redpot Indonesia, an integrated promotional marketing firm that offers innovative promotional products and design services, is where the research is being conducted. This study aims to develop workspaces and workstations that accommodate employees' desires for social interaction and cooperative learning while facilitating productive work environments. Literature reviews, observational studies, and interviews are the data-collecting methods employed.